Influence of Turkey on the policy of neutrality and foreign policy of Turkmenistan (1995–2016) - Khudaiberdieva, Nurbibi Kh. (Journal of the Belarusian State University. History, 2020)
The paper analyzes the attitude of Turkey to the policy of neutrality of Turkmenistan in the period from 1995 to 2016. Based on the geopolitical situation in the Central Asian region in the post-Soviet period, the author identifies the reasons for Turkmenistan’s adoption of a neutral status. Among the reasons for this decision by the Turkmen leadership are the deterioration of the situation in the region, the desire of the great powers and regional leaders to strengthen their positions in Central Asia, including in the energy sector, Turkey’s active position in the post-Soviet period aimed at developing political, energy, and humanitarian contacts, and the desire of The Niyazov regime to limit external influence on the country’s internal and foreign policy. The author noted the influence of the status of neutrality on the implementation of Turkmenistan’s foreign policy and the attitude of Turkey to this process. In the development of Turkmenistan’s neutrality policy in 1995–2016, two stages can be conditionally distinguished: the first is 1995–2006 when the policy of neutrality bordering on isolationism, which seriously limited Turkey’s contacts with Turkmenistan; the second is 2007–2016 when the expansion of cooperation between Turkmenistan and Turkey, including in the security sphere. In the 2007–2016 Turkey sought to expand its geopolitical influence over Turkmenistan by maintaining its neutrality, which led to the formation of a close political and economic dialogue between Ankara and Ashgabat.
Keywords: Turkey; Turkmenistan; neutrality policy; foreign policy; security; Central Asia